2015
DOI: 10.1017/ice.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mandatory Public Reporting of Central Line–Associated Bloodstream Infections on Blood Culture and Antibiotic Utilization in Pediatric and Neonatal Intensive Care Units

Abstract: Mandatory public reporting of central line-associated bloodstream infection did not impact blood culture and antibiotic utilization, suggesting that clinicians have not shifted their practice in an attempt to detect fewer infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Multiple national organizations recommend comprehensive approaches to antimicrobial stewardship (12), and neonatal providers are actively pursuing approaches to optimize antibiotic use among NICU patients (13). In a study using the Pediatric Health Information System database, antibiotic utilization decreased ~5% per year from 2004 to 2012 among hospitals without mandatory public reporting requirements for central line-associated bloodstream infection (14); similar secular trends in NICU antibiotic use were observed among hospitals subject to such reporting requirements. Neonatal antimicrobial stewardship programs at individual centers and collaboratives also report success in safely decreasing overall NICU antibiotic utilization (15-17).…”
Section: Discussionmentioning
confidence: 93%
“…Multiple national organizations recommend comprehensive approaches to antimicrobial stewardship (12), and neonatal providers are actively pursuing approaches to optimize antibiotic use among NICU patients (13). In a study using the Pediatric Health Information System database, antibiotic utilization decreased ~5% per year from 2004 to 2012 among hospitals without mandatory public reporting requirements for central line-associated bloodstream infection (14); similar secular trends in NICU antibiotic use were observed among hospitals subject to such reporting requirements. Neonatal antimicrobial stewardship programs at individual centers and collaboratives also report success in safely decreasing overall NICU antibiotic utilization (15-17).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, blood culture utilization has not been well quantified, and only a few studies have published utilization rates per patient. [14][15][16] While there are some guidelines for blood culture utilization, they do not provide clear indications for obtaining blood cultures, and many recommendations lack a consensus among different professional organizations. [17][18][19] The level of evidence for some recommendations is low, indicating a need for more rigorous evaluations of these existing guidelines.…”
mentioning
confidence: 99%
“…Table 3 provides examples of research publications using different types of administrative data. -Centers for Medicare and Medicaid Services (CMS): MedPar, 69,70 state inpatient databases (SID), 35,52,[71][72][73] Medicaid Analytical eXtract (MAX), 74 Truven Health MarketScan® Multi-State Medicaid Database 75 -TRICARE 76 -University HealthSystem Consortium (UHC) 49 -Kids' Inpatient Database (KID) 77 -Pediatric Health Information System (PHIS) 47 -Premier Perspective 78,79 -Private insurers 11,12 85 -Individual health systems/ consortiums 9,12,23,27,28,37,[86][87][88][89] Surveillance, laboratory, or registry data -Defined as systematic collection of data for a clearly stated purpose -Can include both administrative and clinical data -Programs may allow multiple institutions to pool deidentified data for a common study.…”
Section: Pitfalls and Tipsmentioning
confidence: 99%
“…One prominent example is the increase in laws and regulations related to public reporting of HAI. Several researchers have studied the impact of these laws on blood culture and antibiotic utilization 47 and on central-line–associated bloodstream infection (CLABSI) rates. Interestingly, while hospitals in states with mandatory public reporting were more likely to participate in a national CLABSI prevention program and these participants trended toward greater CLABSI reduction, 48 other investigators have found no difference in HAI reduction in states with mandatory reporting 49 …”
Section: Published Examples In Healthcare Epidemiology and Antimicrobmentioning
confidence: 99%